Wasathiyyah as a Prophetic Practice: A Thematic Study of Hadith on the Principles of Religious Moderation in Indonesia - Yunus, Muhammad; Fadhila, Lu'lu'atus Saniyya Fadhila (UNIVERSUM: Jurnal Keislaman dan Kebudayaan, 2025)
Wasathiyyah is a fundamental principle in Islamic teachings that emphasises balance, ease, and rejection of all forms of extremism. This article examines wasathiyyah as prophetic practice through a thematic study of hadiths on taysir (ease), the prohibition of ghuluw (excessiveness in religion), and social values that support harmony in society. This research uses a qualitative method with a maudhu'i approach, which includes the process of takhrij, criticism of sanad and matan, and contextual meaning analysis. The results of the study show that moderation is not merely a normative concept, but is manifested in the daily practices of the Prophet Muhammad SAW, both in worship, social relations, and in responding to cultural diversity. The findings of the study confirm that the values of taysir and the prohibition of ghuluw form the ethical foundation that shapes the character of the ummah as ummatan wasathan. In the context of Indonesia's multiculturalism, these principles are intertwined with the four pillars of religious moderation, namely national commitment, tolerance, anti-violence, and acceptance of local culture. Therefore, the value of wasathiyyah in the hadith is not only relevant as a spiritual guide, but also as a social framework to strengthen cohesion, prevent polarisation, and maintain harmony amid contemporary religious dynamics. This article emphasises the urgency of revitalising prophetic practices in religious moderation to address the challenges of extremism and disorientation in religious understanding in the digital age.